Analysis of the solid waste management of Guacimo, Costa Rica - Campos-Rodríguez, Rooel (2014)
The aim of this paper its shows the results about the analysis of the solid waste management in the “Municipalidad of Guacimo” located in Limón, Costa Rica. The Municipalidad of Guacimo doesn’t have the basic records and enough information that is necessary for improve the management of the solid waste. Because of that, this investigation provides the inputs for begin to design the solid waste management for the Municipalidad of Guacimo. We search quotes bibliographic about the situation and characteristics of the management of solid waste in Guácimo, we develop the methodology for research and obtain primary information, interview the principal people that work with the solid waste in the Municipalidad of Guacimo and gathering the most important information. We sort and systematize the information about the administration for cleaning the streets and municipal parks, the administration of the collect the solid waste from the streets, schedule and routes of collection, operation of the landfill and the state of the recycle centers. The Guacimo Municipality doesn’t handle appropriately their solid waste, the administration doesn’t have proposals for the adequate management of the solid waste, the budget isn’t enough for collect, transport and disposable the solid waste considering the optimal methods for secure environmental protection, instead, the Municipality contributes to increase the environmental contamination in the area, because the solid waste are dumping in inappropriate site. In this paper, we analyze the interaction among of the politics, organizational culture, management and municipal administration, it’s our wish to provides different alternatives and solutions for improve the waste management in the Municipalidad of Guacimo.